Factors determining the success of sustainable supply chain management in enhancing circular economy capabilities - Yolanda Hutabarat; Titik Kusmantini (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2026)
The transition from a linear economy to a circular economy has become a major focus for small and medium-sized enterprises, particularly in the wood-based furniture sector, which now faces increasingly pressing environmental and sustainability challenges. This study aims to explore the impact of social pressure, environmentally sound economic incentives, and environmental commitment on the capacity to adopt a circular economy, with supply chain relationship management serving as an intermediary variable among small and medium-sized enterprises in Bantul, Yogyakarta. A quantitative approach was applied using Structural Equation Modeling in Partial Least Squares (PLS-SEM), analyzed with Smart-PLS 4.0. Data were collected from 70 small- and medium-sized enterprise owners and managers using structured questionnaires on a five-point Likert scale. The study findings indicate that relational supply chain management plays a crucial role in enhancing circular economy capacity and acts as a bridge between organizational and external factors and circular performance. This study underscores the importance of collaboration within the supply chain in accelerating the shift of small and medium-sized enterprises towards circular practices. The uniqueness of this study lies in combining the Extended Theory of Planned Behavior and sustainable supply chain management to explain circular economy capabilities at the small- and medium-sized enterprise level.